Tiny Habits® for Gratitude-Implications for Healthcare Education Stakeholders - Joshua C. Hollingsworth; David T. Redden (Frontiers Media S.A., 2022)
The COVID-19 pandemic has led to diminished sleep and increased stress, anxiety, and burnout for many health professionals and health professions students. One simple approach that may be effective for bolstering personal well-being is consciously cultivating gratitude. Gratitude is positively associated with physical health, psychological health, hope, sleep, and health behavior engagement; and randomized studies indicate that gratitude interventions can improve psychological well-being and sleep. The primary aim of this study was to assess the impact of practicing Tiny Habits® on self-reported gratitude, as measured by the 6-Item Gratitude Questionnaire (GQ-6). In January 2021, 154 adult participants with GQ-6 <35/42 were randomized to one of 3 groups: Tiny Habits for Gratitude (n = 50), Tiny Habits Control (n = 52), and Inactive Control (n = 52). Both Tiny Habits groups chose 3 Tiny Habits Recipes to practice daily and participated in the free, email-based 5-Day Program with automated daily check-in emails and personalized feedback from a Certified Tiny Habits Coach. The Recipes for the Tiny Habits for Gratitude group focused on cultivating gratitude, while those for the Tiny Habits Control group did not. Post-intervention, the mean change in GQ-6 scores in the Tiny Habits for Gratitude (Δ = ↑6.9 ± 5.6; n = 37/50, 74%; p< 0.001, Cohen's d = 0.85) and Tiny Habits Control (Δ = ↑5.6 ± 4.1; n = 31/52, 60%; p = 0.009, Cohen's d = 0.71) groups were greater than that of the Inactive Control group (Δ = ↑2.5 ± 4.4; N = 42/52, 81%). At 1 month, the mean change in GQ-6 scores in the Tiny Habits for Gratitude group (Δ = ↑7.0 ± 5.3; N = 28/50, 56%) was greater than that of the Inactive Control group (Δ = ↑2.9 ± 5.4; N = 39/52, 72%; p = 0.002, Cohen's d = 0.78). These findings suggest that practicing Tiny Habits Recipes and participating in the 5-Day Program can significantly increase gratitude in the short term and focusing specifically on gratitude during this process can sustain the increase in gratitude for up to 1 month. Implementation is quick, simple, and free. This has significant implications for healthcare education stakeholders.